The influence of state-owned property management, the implementation of the State-Owned Property Management Accounting Information System and human resource competency on the quality of government financial reports - Elsa Apriyanti Aulia; Devyanthi Syarif (eCo-Buss, 2024)
This study explores the complex connection between the management of State Property, the utilization of the State Property Accounting Management Information System, the proficiency of personnel, and their combined influence on the accuracy of financial statements in government organizations. This research seeks to investigate the impact of effective State Property management, facilitated by advanced technological systems such as State Property Management and Accounting Information System, and bolstered by skilled human resources, on the dependability and precision of financial reporting in the public sector. The study will analyze scholarly literature and empirical evidence to achieve this objective. By integrating descriptive and verification methodologies, this research study utilizes a quantitative approach to investigate the influence of human resource competence, the administration of State Property, and the implementation of the State Property Accounting Management Information System on the quality of financial statements within government organizations. The variables are operationalized and measured using indicators that pertain to the quality of government financial accounts, management of State Property, implementation of State Property Management and Accounting Information System, and human resource competency. Data is gathered by distributing questionnaires to the personnel of the Regional Office of the National Land Agency of West Java Province. The total population consists of 54 individuals, and a saturated sampling strategy is used. To summarize, this study highlights the significance of efficient management of State Property and the adoption of State Property Management and Accounting Information System in improving the accuracy and reliability of government financial accounts. Nevertheless, a more thorough examination is necessary to ascertain the exact influence of human resource expertise. These findings enhance the existing information on financial management in the public sector and identify areas where government financial reporting standards might be improved.